Short Communication : Genetic analysis for identification of terminal heat tolerant genotypes in wheat - Mohanty, Soumitra; Mukherjee, Subhra; Dash, A. P.; Mandal, A. B. (The Indian Journal of Genetics and Plant Breeding, 2017)
A study was conducted to analyze divergence in 49genotypes of bread wheat (Triticum aestivum L.) underterminal heat stress environment. The results indicated agood amount of genetic divergence among the wheatgenotypes under heat stress. The genotypes were groupedinto five clusters with maximum intra cluster distance of70.392 (Cluster V) and maximum inter cluster distance wasrecorded between clusters III and V (72.11). Principalcomponent analysis extracted seven principal componentsaccounting 80.9% of total genetic variation. Theidentification of genotypes displaying heat stress tolerancemay be useful in breeding.